A Poem, a Tale, and a Wedding: The Dynamics of the Literary Tradition Surrounding the Marriage of Abraham ibn Ezra to the Daughter of Judah HaLevi - Kfir, Uriah; Rotman, David (MiKAN, 2022)
This article focuses on the famous legend surrounding the marriage of Judah Halevi’s daughter to Abraham ibn Ezra. The first known version of this legend dates back to 1 6111 century Italy, however numerous other versions, each with its own distinctive features, have since been told and published. The eight different versions discussed in this article (hailing from Italy, Yemen, Iraq, Galicia, Tunis, Germany, Morocco and Israel) do not shed new light on the historical figures of Judah Halevi and Abraham ibn Ezra or their actual experiences in 12th century Spain. Rather, they capture what Michel Foucault termed “the name of author,” i.e. how people perceived and imagined these figures in different contexts and the various intertextual links they drew between their poems and the stories they told about them. In this article, the authors demonstrate how each version is never solely a reaction to the poet’s works but also a response to stories told about him over the generations. At the same time, each version constitutes a reflection of the historical and immediate cultural context of its time and place.